2015
DOI: 10.1016/j.ijrobp.2015.05.024
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 3 Trial of 2 Years of Androgen Suppression and Radiation Therapy With or Without Adjuvant Chemotherapy for High-Risk Prostate Cancer: Final Results of Radiation Therapy Oncology Group Phase 3 Randomized Trial NRG Oncology RTOG 9902

Abstract: Purpose Long-term (LT) androgen suppression (AS) with RT is a standard treatment for high-risk, localized prostate cancer (PCa). RTOG 9902 was a randomized trial testing the hypothesis that adjuvant combination chemotherapy (CT) with paclitaxel, estramustine, and oral etoposide (TEE) + LT AS+ RT would improve overall survival (OS). Materials and Methods High-Risk PCa patients (PSA 20–100 and Gleason score (GS) ≥7 or clinical stage ≥T2 and GS ≥8) were randomized to RT and AS (AS+RT) alone or with adjuvant CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 28 publications
0
42
0
1
Order By: Relevance
“…17 Several trials have evaluated tolerance to DTX combined with hormonal therapy and RT for high-risk PCa. 2,18,19 The results of a Phase II trial showed that although feasible, 30% of Grade 3 or higher toxicities was observed. 2 More recently, the GETUG-12 trial found improved relapsefree survival with sequential DTX combined with HT and RT compared with HT alone.…”
Section: Discussionmentioning
confidence: 99%
“…17 Several trials have evaluated tolerance to DTX combined with hormonal therapy and RT for high-risk PCa. 2,18,19 The results of a Phase II trial showed that although feasible, 30% of Grade 3 or higher toxicities was observed. 2 More recently, the GETUG-12 trial found improved relapsefree survival with sequential DTX combined with HT and RT compared with HT alone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the trial was terminated prematurely due to a high rate of thromboembolic events in the chemotherapy arm. 88 Contrary, contemporary studies demonstrated a possible benefit favoring the use of chemotherapy. 75,90,91 In a subset of patients with non-metastatic high risk locally advanced tumors comprising part of the STAMPEDE cohort, docetaxel improved failure-free survival (HR 0.60, 95% CI 0.45–0.80; p<0.001); however, OS analyses were underpowered.…”
Section: Resultsmentioning
confidence: 99%
“…75,88-91 The RTOG 9902 trial assessed whether the addition of paclitaxel, estramustine, and oral etoposide would improve survival in high-risk prostate cancer patients treated with combined RT and long term ADT. The 10-year results revealed no difference in outcome, controlling for tumor stage, Gleason score, and pre-treatment PSA.…”
Section: Resultsmentioning
confidence: 99%
“…The NCTN/NCORP data set is a convenience sample of clinical trial data submitted to the NCTN from studies published after 2015. For all tumor types (except pancreas), publications from 21 clinical trials reported to NCTN/NCORP were reviewed for race/ethnic status (Table ).…”
Section: Methodsmentioning
confidence: 99%